Transcranial Magnetic Stimulation Over the Right Posterior Superior Temporal Sulcus Promotes the Feature Discrimination Processing - Zhou, Qihui; Song, Penghui; Wang, Xueming; Lin, Hua; Wang, Yuping (Frontiers in Human Neuroscience, 2021)
Attention is the dynamic process of allocating limited resources to the information that is most relevant to our goals. Accumulating researches have demonstrated the crucial role of frontal and parietal areas in attention. However, the effect of posterior superior temporal sulcus (pSTS) in attention is still unclear. To address this question, in this study we measured transcranial magnetic stimulation (TMS)-induced event-related potentials to determine the extent of involvement of the right pSTS in attentional processing. We hypothesized that TMS would enhance the activation of the right pSTS during feature discrimination processing. We recruited 21 healthy subjects who performed the dual-feature delayed matching task while undergoing single-pulse sham or real TMS to the right pSTS 300 ms before the second stimulus onset. The results showed that the response time was reduced by real TMS of the pSTS as compared to sham stimulation. N270 amplitude was reduced during conflict processing, and the time-varying network analysis revealed increased connectivity between the frontal lobe and temporal-parietal and occipital regions. Thus, single-pulse TMS of the right pSTS enhances feature discrimination processing and task performance by reducing N270 amplitude and increasing connections between the frontal pole and temporo-parietal, occipital region. These findings provide evidence that the right pSTS facilitates feature discrimination by accelerating the formation of a dynamic network.